2011
DOI: 10.1038/bjc.2011.272
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccination among ethnic minorities in the UK: knowledge, acceptability and attitudes

Abstract: Background:Human papillomavirus (HPV) vaccination offers a unique opportunity for the primary prevention of cervical cancer. Studies suggest that knowledge and attitudes about the vaccine are likely to influence uptake. One limitation of most studies assessing HPV vaccine knowledge, attitudes and acceptability is their under representation of ethnic minorities. It is important to ensure that our understanding of HPV knowledge and attitudes include all ethnic groups in the UK. This article reviews research that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Furthermore, a large number of the community groups contacted for study one were working with BAME communities, which may have impacted on the way in which the study was received. As HPV is sexually transmitted, the topic may be seen as “taboo” or sensitive (Marlow, 2011) and therefore inappropriate to discuss. Furthermore, previous studies have suggested that distrust of scientific investigators and of academic institutions may also act as a barrier to participation for people from BAME backgrounds (Yancy, Ortega, & Kumanyika, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a large number of the community groups contacted for study one were working with BAME communities, which may have impacted on the way in which the study was received. As HPV is sexually transmitted, the topic may be seen as “taboo” or sensitive (Marlow, 2011) and therefore inappropriate to discuss. Furthermore, previous studies have suggested that distrust of scientific investigators and of academic institutions may also act as a barrier to participation for people from BAME backgrounds (Yancy, Ortega, & Kumanyika, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous systematic reviews assessing HPV knowledge in various different populations12–14 55 56 but this is the most up-to-date review that focuses on the primary target group for the HPV vaccine: adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study carried out before the introduction of the HPV vaccine in the UK, uptake was lower in schools with greater ethnic diversity,38 39 and analyses of data from the first year of the vaccination programme (routine and ‘catch-up’ cohorts) also suggest that ethnicity is an important factor in understanding uptake in the UK 35. Research from the UK has also suggested that there is lower awareness and acceptability of the HPV vaccine among ethnic minority groups 40. Future research should explore factors predicting HPV vaccine uptake within ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%